A comparative analysis of the personality patterns of student teachers in teachers' training colleges and in the University of Malaya in Malaysia - Koay, Siew Luan (1977)
This study examined the typical personality profile of Malaysians, specifically teacher trainees. Cattell's 16 Personality Factor Test and the teaching practice grade of the student teachers were used for the study. Results of the study implied distinct personality differences that are noticeable between the various groups investigated. The older more highly qualified group possesses better adjusted personalities.
Appendices: leaves 148-159
Mimeographed.
Thesis (M.Ed.)--University of the Philippines, Quezon City
Vita
Keywords: Student teachers -- Malaysia; Teachers college students -- Malaysia